2015
DOI: 10.1002/2015gl064364
|View full text |Cite
|
Sign up to set email alerts
|

Replicating the 1970s' Weddell Polynya using a coupled ocean‐sea ice model with reanalysis surface flux fields

Abstract: The 1970s' Weddell Polynya is simulated in the framework of a coupled ocean‐sea ice model forced by reanalysis surface flux fields. A rapid emergence of strongly negative wind stress curl over the Weddell Sea intensifies the cyclonic Weddell gyre and thus causes the relatively warm and salty Weddell Deep Water (WDW) to upwell, generating an open‐ocean polynya by melting sea ice or hindering its formation. Once the polynya occurs in the austral winter, the underlying water column is destabilized due to the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…Wind stress supports for the opening of polynya through Ekman upwelling and triggering the formation of convection cells (Gordon & Huber, ). The resulted upwelling of deep warm water plays an important precondition for the occurrence of a long‐lived and large‐scale open‐ocean polynya on the MR (Cheon et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind stress supports for the opening of polynya through Ekman upwelling and triggering the formation of convection cells (Gordon & Huber, ). The resulted upwelling of deep warm water plays an important precondition for the occurrence of a long‐lived and large‐scale open‐ocean polynya on the MR (Cheon et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the formation mechanism of the MR polynya, theoretical and modeling studies has been linked its occurrence to static instability and open-ocean convection (Martinson et al, 1981;Motoi et al, 1987); Taylor column circulation (Alverson & Owens, 1996;Kurtakoti et al, 2018;Muench et al, 2001); cyclonic ocean eddies and atmospheric processes (de Steur et al, 2007;Holland, 2001); strong wind stress (Cheon et al, 2015); interaction between tidal flow, ocean current, and winds (Beckmann et al, 2001); buildup of the oceanic heat reservoir (Dufour et al, 2017); Southern Annular Mode (SAM) and El Niño-Southern Oscillation (Gordon et al, 2007). Most of these studies suggested that the subsurface warm saline water should reach to the upper ocean for the melting of sea-ice and to form a polynya on the MR.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in Figures c and d, the interior of the ice pack in the Weddell Sea is almost unaffected, in agreement with the earlier reports that the Weddell Polynya of the mid‐1970s has not reemerged since [e.g., Gordon et al ., ; Cheon et al ., ]. More importantly, the seasonality of the Antarctic sea‐ice trend in the Atlantic sector is almost perfectly opposite to that in the East Pacific sector (Figures a and b).…”
Section: Antarctic Sea‐ice Trend In the Atlantic Sectormentioning
confidence: 98%
“…During the start of the warming phase of each of the simulated D‐O cycles, the initial instability is coincident with the winter appearance of a large open ocean area measuring more than 10 6 km 2 that is entirely surrounded by sea ice (Figure c). This is approximately 3 times the area of the massive modern‐day Weddell Sea polynya through the period from 1974 to 1976 [ Carsey , ; Martinson et al ., ; Gordon , ; Cheon et al ., ]. In this simulation, deep water formation is able to penetrate to depths between 1500 and 2000 m during winter in the polynya region while the North Atlantic region to the south remains sea ice covered.…”
Section: Analysesmentioning
confidence: 99%